ANALYSIS OF THE MAIN CHANGES TO THE ADMINISTRATIVE IMPROBITY LAW (Reflection and Critique Law Magazine, 2023)
This article aims to analyze the reform brought by the Law no 14.230/21 to the Law no 8.249/92, that regulates the liability of Administrative Improbity acts. Punctuating the main changes and analyzing the effects arising from those changes, using doctrinal and jurisprudential theses, highlighting the consolidation of previous theses and contradiction of others. As well as the approximation of Administrative Improbity with the Administrative Sanctions Law, through the application of its principles, and, consequently, the systematic of Criminal Law. Discussing the subjects that were objects of consideration by the Supreme Court in the first year of the Law no 14.230/21, the constitutionality of some clauses and the principle of retroactivity.